Length-weight relationships and relative condition factor of Parapenaeopsis sculptilis (Heller, 1862) from the coastal waters of Perak, Peninsular Malaysia - Alsayed, Amani Abdulaziz A.; Arshad, Aziz; Md. Yusoff, Fatimah; Sarker, S. M. Nurul Amin Harmuj Ali (Universiti Putra Malaysia Press, 2015)
Length-weight relationship (LWR) parameters and relative condition factor (K n) of marine shrimp, Parapenaeopsis sculptilis (Heller, 1862) were estimated using length-weight data collected between February 2012 and January 2013 from the coastal waters of Terong, Perak, Peninsular Malaysia. The estimated length-weight relationship of P. sculptilis for both sexes was W = 0.00027TL2.80. Meanwhile, the estimated relative growth coefficient (b) was 2.80 for both sexes, indicating a negative allometric growth pattern of P. sculptilis in the investigated area. Relative condition factor (Kn) values ranged from 0.99 to 1.064 (1.013±0.005, mean ±SD). Kn value changes in various months: the highest peak was in March-April, indicating the spawning period and the trough and small peaks indicating the cycle gonadal development.